Effects of Different Mating Strategies on Productive Performance, Bird Welfare and Economic Appraisal of Broiler Breeder under Two Production Systems - Shaheen,MS (2020)
ABSTRACT Objectives of the study were to investigate influence of artificial insemination (AI) in caged and floored flock in comparison to natural mating (NM) on broiler breeders’ welfare, productive performance and economic appraisal. To execute this experiment, a total of 1440 pullets of Ross-308 Parent Stock along with 168 males were picked from a commercial flock and divided into three groups i.e., AIC=AI in cages, AIF=AI on floor and third was NM=NM on floor. Each group carried 480 females (HH) while 168 males were divided into 41, 48 and 58 for AIC, AIF and NM, respectively. During both phases all procedures and studied parameters were the same except the sperm dose rates which were changed during post peak. According to the results, significantly (p≤0.05) higher levels of serum corticosterone, glucose and cholesterol were recorded in birds of AIC and respectively as compared to birds being allowed to mate naturally. Whereas, the experimental males and females of AIF and AIC kept for AI exhibited (p≤0.05) higher body weight, depletion % and feed consumption particularly in post peak phase. However, among the birds subjected to AI, the birds kept in the cages had better performance (p≤0.05) than the birds kept in the floor. Moreover, frequency rate of insemination in females and milking of males found (p≤0.05) reciprocal to the depletion, feed intake and body weight during peak but particularly in post peak. Perhaps, various sperm doses remained inert to implicit any impact on studied parameters. Similarly, egg weight was neither affected by housing systems nor by mating strategies during both phases. However, various insemination and milking frequencies noticeably swayed the productive traits under this study. AI in floored flock was found ineffective even in comparison to natural mating. In conclusion, AI in cages brought forth the better productive performance and lesser male depletion, hence, can be recommended.